Quality Management and Its Implementation at PT. Wika Industri Manufacturing in Producing Electric Motorcycles (GESITS) - Sujoko Winanto; Ahmad Maulidizen; Abdul Haris Muctar; Jaya Jayanto; Muhammad Hasby Fauzi (Proceeding of The International Conference on Economics and Business, 2022)
This article describes the definition of quality management and examples of implementing quality management at PT. Wika Manufacturing Industries in the manufacture of GESITS electric motorcycle products, which we divided into five discussion points. The first is a discussion of the quality basis from the consumer's perspective, commonly referred to as the consumer's perspective, and the quality basis from the side, commonly referred to as the producers' perspective. The second is a discussion of the strategic role of Quality Management with the basic concept of determining excellence so that products can compete optimally when marketed. The third is a discussion of an evolution of the quality paradigm from the Technical to the Managerial Paradigm. The four analyses of quality management are trying to be explored according to experts' understanding and discuss Total Quality Management. The fifth is a detailed discussion of examples of the implementation of quality management at PT. Wika Manufacturing Industry in the manufacture of electric motorcycle products GESITS. And at the end of the discussion, we will provide conclusions about the challenges and strategic issues contained in quality management to answer every challenge in the times